Clinical Outcomes and Complications of Peroneal Tendon Sheath Ultrasound-Guided Corticosteroid Injection. (August 2019) - Fram, Brianna R.; Rogero, Ryan; Fuchs, Daniel; Shakked, Rachel J.; Raikin, Steven M.; Pedowitz, David I.
Background: The treatment of symptomatic peroneal tendinopathy and tears traditionally begins with nonsteroidal anti-inflammatory drugs, activity modification, physical therapy, and immobilization, with surgery typically reserved for those failing nonoperative treatment. Ultrasound-(US)-guided peroneal tendon sheath (PTS) corticosteroid injection is an additional nonoperative modality, but limited data exist on its safety and efficacy. The purpose of this study was to assess clinical outcomes following US-guided PTS corticosteroid injection for chronic tendinopathy or tears. Methods: We retrospectively identified patients who had undergone US-guided PTS corticosteroid injection for pain due to peroneal tendinopathy, tears, or subluxation at our institution from 2012 to 2018. Underlying diagnosis was based on clinical examination, magnetic resonance imaging (MRI) results, and/or intraoperative findings, when available. Medical record data were supplemented by e-mail or telephone follow-up. Collected information included patient age, sex, body mass index (BMI), smoking status, workers' compensation status, prior surgeries about the foot and ankle, duration of symptoms prior to injection, perceived improvement in pain following injection and its duration, number of injections, progression to surgery, and any adverse outcomes of injection. We identified 96 patients (109 injections). Thirty-seven (38.5%) had previous foot and ankle surgery, with 17 (17.7%) having surgery specifically on the peroneal tendons. Results: Twenty-four of 96 (25%) progressed to have surgery on their peroneal tendons following injection. Following injection, 38/87 (43.7%) of patients reported 0-1 weeks of pain relief, 11/87 (12.6%) 2-6 weeks, 6/87 (6.9%) 7-12 weeks, and 32/87 (36.8%) greater than 12 weeks. Preinjection duration of symptoms was associated with postinjection duration of pain relief ( P =.036). There were 2 reported complications (1.8%): 1 case of self-limited sural nerve irritation and 1 of peroneus longus tear progression. Conclusion: Our study demonstrates US-guided PTS corticosteroid injection was safe and relatively effective in patients with symptomatic peroneal tendon tears or tendinopathy, including those who had undergone prior surgery, and may be considered in a comprehensive protocol of nonoperative management. Level of Evidence: Level IV, case series.